2015
DOI: 10.5897/ajmr2014.7286
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and antibacterial properties of selected Nigerian long pepper (Capsicum frutescens) fruits

Abstract: Five varieties of Nigerian long pepper (Capsicum frutescens) fruits (var. baccatum, chacoense, fingerh, maxima and minima) were studied for their antibacterial activities. Methods described by Association of Official Analytical Chemists (AOAC) were employed to determine the phytochemicals in the pepper fruits. The Capsicum frutescens fruits showed antibacterial activity (10.33 -32.66 mm zones of inhibition) against all the tested pathogenic bacteria. The minimum inhibitory concentrations for the peppers range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…The bioactive ingredients could account for the pharmacological potentials of pepper including its antimicrobial activities. Bello et al 16 have reported that 5 varieties of Capsicum frutescens viz: maxima, minima, chacoense, baccatum and finger contain flavonoids, tannins, alkaloids and saponins as active ingredients. Sen et al 19 reported the presence of alkaloids, tannins, flavonoids, saponins, phenol, carbohydrate, protein, reducing sugar and capsaicin in Capsicum annuum, Capsicum frutescens, and Capsicum chinense.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bioactive ingredients could account for the pharmacological potentials of pepper including its antimicrobial activities. Bello et al 16 have reported that 5 varieties of Capsicum frutescens viz: maxima, minima, chacoense, baccatum and finger contain flavonoids, tannins, alkaloids and saponins as active ingredients. Sen et al 19 reported the presence of alkaloids, tannins, flavonoids, saponins, phenol, carbohydrate, protein, reducing sugar and capsaicin in Capsicum annuum, Capsicum frutescens, and Capsicum chinense.…”
Section: Resultsmentioning
confidence: 99%
“…Hot red pepper (Capsicum annuum) and chili pepper (Capsicum frutescence) is characterized by a pungent smell. 15,16 Basically, the nutrient composition chili pepper is influenced by the maturity stage ripe (red) or unripe (green). 17 According to Bello et al 16 capsaicinoid alkaloids found in pepper is responsible for the smell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…frutescens is commonly used as a folk medicine for malaria treatment. Consequently, this study investigated the in vivo antimalarial activity of the plant in an attempt to contribute to the discovery of novel antimalarial drugs using 4-day suppressive test [19,20]. The test is a widely utilized standard in vivo antimalarial screening model in scientific research.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the 80% methanolic crude extract was prepared using cold maceration technique as per to the method described by Bello et al. (19). Accordingly, 500g of coarse powder was soaked in 750 ml of 80% methanol solution using an Erlenmeyer flask.…”
Section: Preparation Of the Crude Extractmentioning
confidence: 99%